Does Islamic Finance fulfill the objectives of Maqasid Al-Shari’ah? - Kamarudin, Ainatul Aqilah; Kassim, Salina; Imon, Riasat Amin; Xian, Seow Yi (International journal of economic perspectives, 2026)
This study examines whether Islamic finance is fulfilling the objectives of Maqasid al-Shari’ah. It adopts qualitative analysis, where an in-depth interview session with 7 experts in the industry is undertaken. The findings are classified into 3 themes; 1) Information on the Islamic banking-growth nexus, 2) Information on the Islamic capital market-growth nexus, and 3) Information on the Takaful-growth nexus. The first theme shows that although Islamic Banking (IB) sector is gradually moving towards equity financing, it is still highly-dependent on debt-financing. The second theme shows that Islamic Capital Market (ICM) is significantly contributing to the ESG via the implementation of SRI Sukuk, Bond Grant Scheme, ESG Financing/Sukuk, and value-based judgement projects. The final theme shows that Takaful industry has contributed its own humble quota to economic growth by creating jobs to the society and adding values to both participants and businesses. The work gives some insights into the field of Islamic finance in the light of Maqasid al-Shari’ah from the perspective of a developing country, which is Malaysia.